Designing Behavioral Interventions That Work: The Triple T – Triple R Competing Pathways Model - Karen L Gischlar; Laura A Riffel (Educational Considerations, 2020)
Increasing numbers of children are entering our nation’s schools with mental or behavioral health problems. Although many of these children are included in general education programs, teachers report feeling under- or unprepared to manage problematic behaviors. This is not surprising given that reviews of teacher training programs have evidenced limited coursework in classroom management. Within this paper, we present a framework, the Triple T – Triple R Competing Pathways Model, that is grounded in the tenets of Applied Behavior Analysis (ABA). ABA has decades of empirical evidence to support its use in the classroom. Triple T – Triple R simplifies the competing pathways chart frequently utilized within ABA, rendering our model accessible to teachers who might not have previous training or experience with application of behavioral tenets.
Keywords: behavior; interventions